Soluble fms-like tyrosine kinase 1 and placental growth factor ratio for predicting preeclampsia in elderly gravida - Vorapong Phupong; Wilasinee Areeruk; Patau Tantbirojn; Ruangsak Lertkhachonsuk (Taylor & Francis Group, 2020)
Objective To determine the predictive value of plasma soluble fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF) ratio for detection of preeclampsia in elderly gravida at 16-18 weeks of gestation and to identify whether abnormalities of this ratio are associated with any other pregnancy complications or not. Methods Blood samples of 300 cases were collected. Plasma sFlt-1 and PlGF levels were measured using an automated immunoassay. Results  Sensitivity and specificity for plasma sFlt-1/PlGF ratio above 9.8 for preeclampsia prediction were 85.7% and 61.2%, respectively. The sensitivity and specificity to predict early onset preeclampsia were 100% and 61.1%, respectively. Women with abnormal plasma sFlt-1/PlGF ratio were not associated with any other pregnancy complications. Conclusion  sFlt-1/PlGF ratio at 16-18 weeks of gestation in elderly gravida has a high sensitivity for predicting preeclampsia, especially early onset preeclampsia.